Studi Literatur Riset Ekonomi dan Keuangan Islam dalam Jurnal Terindeks Scopus Q1 - Aam Slamet Rusydiana (AL-MUZARA'AH, 2020)
This study tries to review the research around Islamic economics and finance on reputable journal. It uses descriptive statistical analysis based on selected 177 article publications or paper related to Islamic economics and finance, with international journal indexed by scopus Q1. The entire sample journal publications have published for five years from 2014 to 2018. The results show that Islamic economics and finance research is still dominated by Islamic banks issues (42%), followed by Islamic capital market issues (31%), then Islamic accounting (9%), Islamic business and marketing (7%), Islamic monetary (4%), and other Islamic economics and finance issues (7%), like takaful, microfinance, halal industry, waqf and economic of hajj. In addition, the average time of journal publication is between 9 and 10 months. There are at least 20 Q1 scopus journals that publish Islamic economics and finance articles and the most research with Pacific-Basin Finance Journal, Journal of Economic Behavior & Organization, Journal of International Financial Market, Institution & Money, and Journal of Business Ethics. Furthermore, the comparison of quantitative research (84%) is still more than the qualitative approach (16%).